A bio-inspired high strength three-layer nanofiber vascular graft with structure guided cell growth. Issue 20 (3rd May 2017) - Liu, Kai; Wang, Nü; Wang, Wenshuo; Shi, Lianxin; Li, Hao; Guo, Fengyun; Zhang, Lihua; Kong, Liang; Wang, Shutao; Zhao, Yong
Abstract : A bio-inspired three-layer vascular graft with strong mechanical properties and good cell biocompatibility was fabricated by electrospinning. It will play an important role in vessel remodeling and regeneration. Abstract : Human natural blood vessels have a three-layer structure including the tunica intima, tunica media, and tunica adventitia . These subtle structures endow healthy blood vessels with outstanding strength, elasticity, and compliance as well as excellent haemodynamic and anti-thrombus performance. Fabrication of a next generation vascular graft that mimics the structures and functions of natural blood vessels is becoming the pursuit of biomaterials and medical scientists. Here we fabricate a bio-inspired nanofiber three-layer vascular graft by electrospinning. The inner PLA/PCL layer is favorable for adhesion of human umbilical vein endothelial cells that could accelerate endothelialization. The middle PU/PCL layer provides superior mechanical properties (63.40 MPa, 266.78% in the longitudinal direction and 52.34 MPa, 319.72% in the lateral direction). The outer PLA/PCL layer with circumferentially aligned fibers is beneficial for guiding vascular smooth muscle cells in the circumferentially oriented direction. The bio-inspired three-layer vascular graft with strong mechanical properties and good cell biocompatibility will play an important role in vessel remodeling and regeneration.